An Economic History of Cambodia in the Twentieth Century - Slocomb, Margaret (NUS Press, 2010)
While colonization, protracted war and violent revolution are commonly blamed for Cambodia's failure to modernize its economy in the twentieth century, Margaret Slocomb's Economic History of Cambodia in the Twentieth Century questions whether these circumstances changed the underlying structures and relations of production. She also asks whether economic factors in some way instigated war and revolution. In exploring these issues, the book tracks the erratic path taken by Cambodia's political elite and colonial rulers to develop a national economy. The book closes around 2005, by which time Cambodia had be reintegrated into both the regional and into the global economy as a fully-fledged member of the World Trade Organization.Drawing on resources from the State Archives of Cambodia, this book is relevant to investors, aid workers and development specialists seeking to understand the shift from a traditional to a modern market economy.